Estimate of Impact on the Oral Health-Related Quality of Life of Older Thai People by the Provision of Dentures through the Royal Project - Patcharawan Srisilapanan; Narumanas Korwanich; Sutha Jienmaneechotchai; Supranee Dalodom; Nontalee Veerachai; Warangkana Vejvitee; Jeffrey Roseman (Hindawi Limited, 2016)
Purpose. To estimate the impact of the provision of dentures to Thai older people by the Royal Project on their oral health-related quality of life. Methods. A purposive cross-sectional study of a sample of 812 subjects was conducted. The Oral Impacts on Daily Performances (OIDP) measure was used to assess the oral health-related quality of life. Results. Four groups of older people with different tooth types were studied. 216 (26.6%) had natural teeth (NT). 189 (23.3%) had natural and replaced teeth (NRT). 167 (20.6%) had below the minimum number of teeth but had no dentures (Edent) and 240 were edentate with complete dentures provided by the Royal Project (ECD) (29.6%). Overall, 36.5% had at least one oral impact. Eating was the most affected oral impact. When compared to the group with natural teeth (NT), the Edent group was significantly more likely to report having impacts on eating OR = 6.5 (3.9-10.9), speaking clearly OR = 43.7 (12.7-15.07), emotional stability OR = 16.5 (6.0-45.6), and social contacts OR = 4.6 (2.2-9.5) (p<0.001). Conclusion. Those who are edentulous are much more likely to have an oral impact on their daily performances than those provided dentures. Provision of dentures may lead to improvement of considerable oral impacts.